A caça em marcha: leituras e edição crítica do livro Antes do baile verde, de Lygia Fagundes Telles - Resende, Nilton José Melo de (2013)
In 1970, Lygia Fagundes Telles published the book Antes do Baile Verde, disclosing previously unpublished tales and short stories, reviewed by the author herself for this new edition, beginning the creation of a personal canon, by excluding some texts and altering those which remained. That being so, this book emerges as a kind of critic to her own work - criticism that is true not only because of the tales reviewing, but also for the reviewing of the book itself, which configuration has been changing for more than a decade, until reaching its current version. This shows us a constant movement as a writer on pursuit of an never achievable perfection. The work here presented is an attempt undertaken by a "model reader" to understand the intent of a hypothetical "model author" by modifying the tales here gathered and studied - according to the researcher Umberto Eco (1994). Besides Eco, we based ourselves on other novelists, also theoretical, such as Alberto Manguel (2005), Osman Lins (1974), Ricardo Piglia (2006), which addressed the issue of construction and reading of literary texts; and the work of Lygia Fagundes Telles, specifically: Alfredo Monte (2013), Nelly Novaes Coelho (1971), Vera Maria Tietzmann Silva (1985 and 2009), Vicente Ataíde (1972). In that search, we looked quantitatively and qualitatively upon tales review presented before the book Green Ball, examining how some recurring elements were gradually incorporated into the narrative, giving them an authorial homogeneity. The changes seen in the tales are of different natures: employment of more conversational tone; update of words; greater adaptation of language to the characters; option for buildings that do not call too much attention to themselves; larger economy in the construction of the scenes and characters; etc. Such changes can be perceived in the critical edition through the comparison between the first and last issues of each of the stories in this book. Here, we give the reader the latest edition of these tales, bringing, beside them, modified excerpts, as they appeared in their primary editions, presented on books from 1949 to 1970.